( 1 + α 2 ) ( 1 + β 2 ) ( 1 + γ 2 ) ( 1 + δ 2 )
If α , β , γ , δ are the roots of the equation x 4 + 4 x 3 − 6 x 2 + 7 x − 9 = 0 , then find the value of the above expression.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Shouldn't it be LaTeX: ( x − α ) ( x − β ) ( x − γ ) ( x − δ ) = x 4 + 4 x 3 − 6 x 2 + 7 x − 9
Log in to reply
oh sorry updated it.. I think I was sleeping when I posted it.. lol
Equation can be written as:- x 4 − 6 x 2 − 9 = − x ( 4 x 2 + 7 ) ⟹ ( x 4 − 6 x 2 − 9 ) 2 = x 2 ( 4 x 2 + 7 ) 2 ⋯ ( 1 ) 1 + α 2 = x ⟹ α = x − 1 Since α is a root of the equation ( 1 ) : ∴ ( ( x − 1 ) 2 − 6 ( x − 1 ) − 9 ) = ( x − 1 ) ( 4 ( x − 1 ) + 7 ) 2 ⟹ ( ( x − 1 ) 2 − 6 ( x − 1 ) − 9 ) − ( x − 1 ) ( 4 x + 3 ) 2 = 0 We have to find the product of roots of this equation since its roots are 1 + α 2 , 1 + β 2 , 1 + γ 2 , 1 + δ 2 which can be calculated by Vieta's formula and since leading coefficient is 1 we only have to find the constant term which is given by:- 1 + 3 6 + 8 1 + 1 2 − 1 0 8 − 1 8 + 9 = 1 3
This is a nice solution. Thanks for sharing!
Log in to reply
Ya .... I thought that this approach also need to be shared.. :-)
Problem Loading...
Note Loading...
Set Loading...
We can write
( x − α ) ( x − β ) ( x − γ ) ( x − δ ) = x 4 + 4 x 3 − 6 x 2 + 7 x − 9
putting i and − i in x and multiplying the equations,
( i − α ) ( − i − α ) ( i − β ) ( − i − β ) ( i − γ ) ( − i − γ ) ( i − δ ) ( − i − δ ) = ( − 2 + 3 i ) ( − 2 − 3 i )
( 1 + α 2 ) ( 1 + β 2 ) ( 1 + γ 2 ) ( 1 + δ 2 ) = 1 3